Assessing the Effectiveness of the Picture and Picture Model in Teaching Prayer Movements in Islamic Religious Education - Khoirul Anwar; Ubaidillah Ubaidillah (STAI Hubbulwathan Duri, 2024)
This study aims to investigate the implementation and effectiveness of the Picture and Picture learning model in enhancing Grade II students’ understanding of prayer movements at MIN 2 Jember. This approach is considered to help young learners better visualize and comprehend the sequence of prayer movements through structured visual aids. A qualitative case study approach was used, with data collected from interviews and documentation. Participants included teachers, students, and the principal, providing a comprehensive view of the learning model’s application and impact. Findings indicate that the Picture and Picture method significantly improves students' grasp of prayer movements. By arranging sequential images, students develop a clearer understanding of each step involved in the prayer sequence. Indicators of effectiveness include students' ability to organize images correctly, explain the movements, demonstrate conceptual understanding, and actively participate in class activities. The study demonstrates that using the Picture and Picture model enhances students' learning by promoting visualization, active engagement, and critical thinking. This method not only helps in understanding complex religious concepts but also encourages interaction and deeper comprehension. The Picture and Picture method effectively supports young learners in visualizing and internalizing prayer movements, making it a valuable tool for educators teaching complex concepts. Its application across subjects could foster critical thinking and active learning among elementary students.